Application of Web-based for E-business - E S Soegoto; E Mustafa (Universitas Komputer Indonesia, 2021)
E-commerce is one of the technologies that should be applied in a company. The objective of this study is to identify e-commerce growth in improving competitive advantage in business processes. The method used was descriptive method for presenting a complete one picture of the social setting or intended for exploration and clarification of a phenomenon or social reality, by describing number of variables relating to the problem and the unit under study between the phenomena being tested. The results of this study were to increase the competitive advantage of the company. This study was conducted by discussing the payment transaction system, sales, and orders made by businesses using e-commerce technology. If all things are well-conducted, it can increase the competitive advantage of the company